Structural performance and design of corrugated steel tunnels - Nashwa Nabil Ibraheem Soliman; Sherif Ahmed Mourad; Ahmed Hosny Moh. Abdel Rahman; Sherif Adel Yehia Akl (2025)
Flexible soil-steel composite structures technology depends on the interaction between surrounding backfilling and the corrugated flexible steel plates. The thesis purpose is to investigate shallow buried large span Soil Steel Composite Bridges (SSCBs). A numerical parametric study is carried out using the PLAXIS 3D finite element program to explore several topics regarding the large span SSCBs performance. Firstly, the study investigates the effect of some site/construction circumstances on open arched profile SSCBs performance. Secondly, the study checks the impact of changes in profile aspect ratios and backfilling soil mechanical properties on large span SSCB performance. FE results reveal their effect on the induced arching mechanism and straining actions. Finally, the study checks the validity of existing design codes for large span SSCBs, where the results prove that they cannot estimate proper straining actions for large spans. Thus, the study proposed modified equations for calculating better-estimated straining actions.
(3JYJeO GdCfaGb GdeQcHI GdeQfI HTcd CSGSj Ydi GdJCKjQ GdeJHGOd Hjf GdJQHI GdeMjWI hGdCdhGM GdUdH GdeJYQLI(B. (3JgOa gPg GdQSGdI Edi OQGSI GdLShQ GdeQcHI ef GdUdH hGdJQHI (B(SSCBs) (3PGJ GdHMhQ GdcHjQI(B. (3h Pdc ef NdGd ELQGA OQGSI YOOjI HGQGeJQjI HGSJNOGe HQfGeL GdYfGUQ GdeMOhOI (BPLAXIS 3D. (3ChdkG, Je OQGSI JCKjQ HYV GdXQha GdNGUI HGdehbY (B/ (3GdHfGA Ydi COGA Gdfab GdebhS GdeaJhM(B. (3Ke JeJ OQGSI JCKjQ GdJZjjQ aj fSH CHYGO Gdfab hNUGFU JQHI GdQOe Ydi GdLShQ GdeQcHI ef GdUdH hGdJQHI PGJ GdHMhQ GdcHjQI(B. (3CKHJJ GdfJGFL JCKjQ GNJdGa fSH CHYGO GdbWGY h NUGFU JQHI GdQOe Ydi BdjI GdJbhS h bjeI GdCaYGd GdeDKQI GdfGJLI(B. (3hCNjkQG, Je GdJMbb ef UdGMjI GdCchGO GdJUejejI GdMGdjI ddLShQ GdeQcHI ef GdUdH hGdJQHI PGJ GdHMhQ GdcHjQI(B. (3h CXgQJ GdfJGFL Cf gPg GdeYGOdGJ HMGLI Edi GdJMOjK dMSGH bje CcKQ ObI ddCaYGd GdeDKQI GdfGJLI Ydi GdCfaGb PGJ GdHMhQ GdcHjQI(B. (3Ke GbJQMJ GdOQGSI eYGOdGJ eMOKI dMSGH GdCaYGd GdeDKQI GdfGJLI aj GdCfaGb PGJ GdHMhQ GdcHjQI(B.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 179-182.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Spending; (3GdGfaGb s; Soil Steel Composite Bridges -- Arching mechanism -- Large span tunnels -- Induced straining actions -- Finite element method